SUCCESSFUL DELIVERY OF A SCHISTOSOMUS REFLEXUS MONSTER IN A NON-DESCRIPTIVE DOE: CASE REPORT - S. Radhika; M. Srinivas; B. Chandra Prasa; N. Nagarjuna (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A four-year old fullterm pregnant doe in its third parity was presented to the obstetrical ward with the history of unproductive straining for the past 24 hours. Physical examination revealed that the doe was anorectic, dehydrated, and had moderate rise in body temperature. Trans-abdominal ultrasonography confirmed the presence of an abnormal dead fetus. Per-vaginal examination revealed that the cervix had incomplete dilatation. Hence, the cesarean section was opted to relieve the dead fetus. After cesarean section, the defective fetus was found to be schistosomous reflexus monster. Postoperatively, the doe had an uneventful recovery, indicative of a successful surgical outcome.